On the Lebesgue constants - Kushpel, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.5 We give the solution of a classical problem of approximation theory on sharp asymptotic of the Lebesgue constants or norms of the Fourier – Laplace projections on the real spheres S^d, complex P^d(C) and quaternionic P^d(H) projective spaces, and the Cayley elliptic plane P^16(Cay). In particular, these results extend sharp asymptotic found by Fejer in the case of S^1 in 1910 and by Gronwall in 1914 in the case of S^2 .